Existence and uniqueness of mild solutions for impulsive semi linear differential equations in a Banach space - Berrezoug Halimi, Khelifa Daoudi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This paper is devoted to study the uniqueness and existence of mild solutions for impulsive semilinear differential equations, we assume that the linear part generates a strongly continuous semigroup on a general Banach space in a Banachspace. The arguments are based upon Banach’s, Mönch’s and Darbo’sfixed point theorems and the technique of measure of noncompactness. Finally, an illustrative example is given to illustrate the results.